Dietary management and growth outcomes in children with propionic acidemia: A natural history study - Haneen Saleemani; Csilla Egri; Gabriella Horvath; Sylvia Stockler‐Ipsiroglu; Rajavel Elango (JIMD Reports, 2021)
Abstract Background Propionic acidemia (PROP) is an autosomal recessive inherited deficiency of propionyl‐CoA carboxylase (PCC) which is involved in the catalytic breakdown of the amino acids valine, isoleucine, methionine, and threonine. PROP nutritional management is based on dietary protein restriction and use of special medical formulas which are free of the offending amino acids, but are enriched in leucine. The resulting imbalance among branched‐chain amino acids negatively impacts plasma concentrations of valine and isoleucine, which might impact growth in children with PROP. Objective and Methods Our primary objective was to describe dietary protein and calorie intake and their impact on long‐term growth outcomes of four PROP patients. This was accomplished through a longitudinal retrospective chart review following the cohort from birth to 18 years. Results All children (n = 4) had poor growth outcomes with persistently reduced height‐for‐age Z scores, and elevated weight and body mass index (BMI) Z scores. Energy intakes for all subjects were within 80% to 120% of the dietary reference intakes for age. All children had low intakes of intact protein compared with current guidelines and were supplemented with medical formula and single l‐amino acids (valine and/or isoleucine), which led to the excess consumption of total protein. Conclusion Despite adequate total protein and energy intakes, all children had persistently low height Z scores. Restricted intact protein consumption together with the abundant use of medical formula could have affected overall growth. To optimize dietary management in patients with PROP, further research is needed to determine the optimal intake of medical formula relative to intact protein.